A systems approach identifies Enhancer of Zeste Homolog 2 (EZH2) as a protective factor in epilepsy. - Nadia Khan; Nadia Khan; Barry Schoenike; Trina Basu; Heidi Grabenstatter; Genesis Rodriguez; Caleb Sindic; Margaret Johnson; Eli Wallace; Rama Maganti; Raymond Dingledine; Avtar Roopra (PLoS ONE, 2019)
Complex neurological conditions can give rise to large scale transcriptomic changes that drive disease progression. It is likely that alterations in one or a few transcription factors or cofactors underlie these transcriptomic alterations. Identifying the driving transcription factors/cofactors is a non-trivial problem and a limiting step in the understanding of neurological disorders. Epilepsy has a prevalence of 1% and is the fourth most common neurological disorder. While a number of anti-seizure drugs exist to treat seizures symptomatically, none is curative or preventive. This reflects a lack of understanding of disease progression. We used a novel systems approach to mine transcriptome profiles of rodent and human epileptic brain samples to identify regulators of transcriptional networks in the epileptic brain. We find that Enhancer of Zeste Homolog 2 (EZH2) regulates differentially expressed genes in epilepsy across multiple rodent models of acquired epilepsy. EZH2 undergoes a prolonged upregulation in the epileptic brain. A transient inhibition of EZH2 immediately after status epilepticus (SE) robustly increases spontaneous seizure burden weeks later. This suggests that EZH2 upregulation is a protective. These findings are the first to characterize a role for EZH2 in opposing epileptogenesis and debut a bioinformatic approach to identify nuclear drivers of complex transcriptional changes in disease.